Are green bonds a viable way to finance environmental goals? An analysis of chances and risks of green bonds - Markus Demary; Adriana Neligan (Institut der deutschen Wirtschaft (IW), 2018)
The European Union is currently making significant strides to lead on green finance and align its financial system with its climate, sustainability and clean energy ambitions. The Paris Climate Agreement, the G20 Green Finance Study Group and the G19 Hamburg Climate and Energy Action Plan have provided ongoing momentum for policy moves towards a green financial system. Including financial markets into a climate strategy is a logical step forward, because public funds are insufficient to finance the needed investments in green technology and because the financial sector shows interest in financing green technology. Given the long-term nature of green investments and the financial market's short-termism, the establishment of a liquid market for green bonds is the market solution to this maturity mismatch. However, for such a market to thrive, investors need a definition of green technology as well as a definition of what a green bond is. In addition to that, green disclosure rules are needed, so that investors can easily access information on how the proceedings of green bonds are invested. The EU's main efforts in establishing a market for green bonds are the legislation of a common taxonomy for green bonds and the stimulation of the demand for green bonds by a green supporting factor in bank capital regulation. While we agree that a common taxonomy will help investors to screen green projects, we are very sceptical about the green supporting factor, which causes lower equity capital requirements for green investments. We see the risk that this may give rise to an undercapitalisation of banks with respect to the default risks of green projects and an overinvestment of banks into these projects. Since the green bond market is a political project, there is the danger of privileging green bonds in financial regulation for achieving political goals. The emergence of a green bond bubble and the bursting of that bubble would be harmful to the financial sector and it would hinder reaching the climate goals, since investors will abstain from investments in which they have lost money before. We derive the risk of political interventions to stimulate the demand for green bonds from our estimates, which indicate that annual green bond emissions have to grow by the factor 45 in order to finance the potentially needed overall annual investments of up to USD 7 trillion making a higher indebtedness or significant portfolio shifts necessary. Looking only at incremental investments needs to reach the climate goal green bond issuance would also have to increase up to the factor 4.5 and to reach the Sustainable Development goals by the factor 15. Instead of pushing for a fast growth of the green bond market, the EU should strive for its organic growth. Therefore, it should rely on market intelligence, i.e. the market participant's risk assessments for the green projects' default risks together with the market participants evalua-tion of the greenness of green investment projects. To this end, the proposed harmonisation of the taxonomy within the EU is a necessary step, because different national taxonomies would hinder the emergence of cross-border markets for green bonds. The EU cared about the con-sistency of the green bond proposal with other regulations for financial institutions, but it would be necessary to guarantee consistency also in the future. Otherwise, unintended side effects could distort the investment decisions of financial companies.
Keywords: E22; G11; G12; O16; Q01; Q54; Q56; 330